Síndrome de Burnout y rendimiento académico en estudiantes de la Carrera de Enfermería de la Universidad Nacional de Loja - Astudillo Peña, Jefferson Andrés (2023)
The academic work of a university student from Human Health School, is demanding and exhausting to the point that it can trigger Burnout syndrome. The general objective of this research work was to determine Burnout syndrome and academic performance in nursing students of Universidad Nacional de Loja. A quantitative study was developed. The Maslach Burnout Questionnaire for Students (MBI-GS(S)) was applied to a sample of 137 participants, 75.1% of whom were female and 24.8% male. A prevalence of 49.64% of Burnout syndrome was obtained, being mainly affected the dimension of Exhaustion 28.47% followed by Academic Effectiveness 26.28% and finally Cynicism 10.22%. As for academic performance there is a predominance of the rating of Very Good 59.85%, followed by the rating Good 38.69% and finally Poor with 1.46%. The academic cycle with the most cases of Burnout syndrome was Fifth grade 17.52%, the cycle with the fewest cases was Second grade with a prevalence of 5.11%. A greater relationship was evidenced between Very Good academic performance and the presence of Burnout syndrome with 32.85%, however, no statistically significant association was shown between both variables with p>0.05. Therefore, we can conclude that there is the presence of Burnout syndrome without showing a relationship with academic performance